Chronic ankle instability is associated with proprioception deficits: A systematic review and meta-analysis - Xiao'ao Xue; Tengjia Ma; Qianru Li; Yujie Song; Yinghui Hua (Elsevier, 2021)
Background: Acute ankle injury causes damage to joint mechanoreceptors and deafferentation and contributes to proprioception deficits in patients with chronic ankle instability (CAI). We aimed to explore whether deficits of proprioception, including kinesthesia and joint position sense (JPS), exist in patients with CAI when compared with the uninjured contralateral side and healthy people. We hypothesized that proprioception deficits did exist in patients with CAI and that the deficits varied by test methodologies. Methods: The study was a systematic review and meta-analysis. We identified studies that compared kinesthesia or JPS in patients with CAI with the uninjured contralateral side or with healthy controls. Meta-analyses were conducted for the studies with similar test procedures, and narrative syntheses were undertaken for the rest. Results: A total of 7731 studies were identified, of which 30 were included for review. A total of 21 studies were eligible for meta-analysis. Compared with the contralateral side, patients with CAI had ankle kinesthesia deficits in inversion and plantarflexion, with a standardized mean difference (SMD) of 0.41 and 0.92, respectively, and active and passive JPS deficits in inversion (SMD = 0.92 and 0.72, respectively). Compared with healthy people, patients with CAI had ankle kinesthesia deficits in inversion and eversion (SMD = 0.64 and 0.76, respectively), and active JPS deficits in inversion and eversion (SMD = 1.00 and 4.82, respectively). Proprioception deficits in the knee and shoulder of patients with CAI were not statistically significant. Conclusion: Proprioception, including both kinesthesia and JPS, of the injured ankle of patients with CAI was impaired, compared with the uninjured contralateral limbs and healthy people. Proprioception varied depending on different movement directions and test methodologies. The use of more detailed measurements of proprioception and interventions for restoring the deficits are recommended in the clinical management of CAI.